THE EFFECTS OF HERBS ON MILK YIELD AND MILK QUALITY OF MASTITIS DAIRY COW - Nurdin, E.; Amelia, T.; Makin, M. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
This experiment aimed to observe the effect of herbs (Black Cumin,Curcuma zeodharia,Curcumamangga, and Curcuma aeruginosa) supplementation on milk yield and milk quality (milk fat, milkprotein, milk lactosa and mastitis status) in lactating dairy cows suffering mastitis. Twenty cows in 2nd-4th lactation suspected mastitis subclinical (++) were used in the experiment. Completely randomizeddesign was used in this experiment with 5 treatments (A. Non Herb; B. Black Cumin; C. Curcumazeodharia; D. Curcuma mangga, and E. Curcuma aeruginosa) with four replicates per treatment. Thecollected data were analyzed by analysis of variance and difference between the treatment effects wastested by using Duncan’s Multiple Range Test. The results showed that supplementation of herbssignificantly increased (P<0.01) milk yield, milk protein, milk lactosa and significantly decreasedmastitis status and did not significant affect milk fat.